2022
DOI: 10.1021/acs.orglett.2c03185
|View full text |Cite
|
Sign up to set email alerts
|

Construction of [2,5]-Furanophanes by Carbene-Mediated Alkynyl Migration Cyclization

Abstract: Heterophanes are widely found in natural products and drug molecules. Herein, an efficient method for the construction of [2,5]-furanophanes with different ring types and ring sizes was developed. This method is carried out with furan-free precursor through intramolecular carbene-mediated alkynyl migration and tandem cyclization strategy. In addition, a series of tetrafuran structures can be obtained by oxidative coupling of the products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…The same group later reported a domino process using propargyl alcohol-tethered enynals 76 to synthesize 12-to 15membered [2,5]-furanophanes 77 via furyl platinum carbene formation, semi-pinacol rearrangement, and 5-endo-dig cyclization (Scheme 29). [43] In the presence of PtCl…”
Section: Domino Reaction Involving Semi-pinacol Rearrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group later reported a domino process using propargyl alcohol-tethered enynals 76 to synthesize 12-to 15membered [2,5]-furanophanes 77 via furyl platinum carbene formation, semi-pinacol rearrangement, and 5-endo-dig cyclization (Scheme 29). [43] In the presence of PtCl…”
Section: Domino Reaction Involving Semi-pinacol Rearrangementmentioning
confidence: 99%
“…The same group later reported a domino process using propargyl alcohol‐tethered enynals 76 to synthesize 12‐ to 15‐membered [2,5]‐furanophanes 77 via furyl platinum carbene formation, semi‐pinacol rearrangement, and 5‐endo‐dig cyclization (Scheme 29). [43] In the presence of PtCl 2 , furyl metal carbene intermediate I undergoes 1,2‐alkynyl migration via semi‐pinacol rearrangement, forming zwitterionic intermediate II with an expanded ring size. Proton transfer and Pt re‐coordination generate intermediate III , followed by intramolecular 5‐endo‐dig cyclization to yield heterophane 77 containing two furan rings.…”
Section: Furyl Metal Carbene X−h Insertion Reactions Using Enynones O...mentioning
confidence: 99%
“…The furan-containing polycyclic moiety has widely existed in natural products and bioactive compounds, such as Gnetifolin F, Salvileucalin C, and (+)-6, 11-epoxy-isodaucane (Scheme d) . In addition, with our continuous work in alkyne chemistry and inspired by our recent work on the Rh­(II)-catalyzed cycloisomerizations of enyne and diyne, especially for the discovery of the favorable [3 + 2] cycloaddition with alkynal as the neutral three-atom component, we found that 1,5-enynal could undergo the [3 + 2] cycloaddition successfully under the catalysis of dirhodium and act as the right precursor to give the endocyclic vinyl Rh-carbene, which could be trapped by a diversity of alkenes to produce the spiro and polycyclic dihydrofurans with good diastereoselectivities (Scheme e). Notably, up to three new rings and three new stereocenters were constructed in one step.…”
Section: Introductionmentioning
confidence: 99%
“…These retrosynthetic analyses using two intramolecular cycloadditions of 1,3-dipoles led to a 10-membered cyclic diene as a precursor. The diene moiety in III could be prepared via enyne metathesis of 10-membered cyclic alkyne IV , , which could in turn be derived from a malonate ester.…”
mentioning
confidence: 99%